Gain variation induced by power transient in thulium-doped fiber amplifier at 2µm and its reduction by optical gain clamping technique - Karin Ennser (Optics Communications, 2017)
This paper investigates the dynamic behavior of a thulium doped fiber amplifier (TDFA) operating in the 2 µm region for reconfigurable wavelength division multiplexing (WDM) systems. We show deleterious channel power fluctuations may be generated by input power variation at the amplifier and we propose the use of an optical gain-clamping technique. The investigated system consists of 20 channels with −4 dBm total input power. Our findings revealed that the effects of power transients due to channel reconfigurations are significantly reduced by a lasing feedback signal. Simulation results show that a power excursion of 4.3 dB is produced after dropping 19 channels when the amplifier gain is unclamped and only 0.0062 dB when the amplifier gain is clamped. The dynamics of GC-TDFA are mainly influenced by the value of the pump power factor and thus the laser signal achieves a stronger stabilization condition with increasing pump power factor. Hence, optical gain clamping is a simple and robust technique to control the power transient in the thulium-doped fiber amplifier of WDM systems at 2 µm.